What convinces donors? An analysis of donation‐based crowdfunding projects from nonprofit charities: The case of South Korea. Issue 4 (7th December 2021) - Kim, Soobin; Kang, Chulhee; Engel, Rafael
Abstract: Despite the potential usefulness of donation‐based crowdfunding as a fundraising tool for nonprofit social welfare organizations, academic understanding of what leads to a successful campaign is limited. Drawing on an information processing model, this research analyzes 889 donation‐based crowdfunding campaigns undertaken by nonprofit social welfare organizations using HappyBean, the most representative crowdfunding platform in South Korea. This study examines whether different types of project information influence the percentage of individual donors giving to the campaign's funding goal. Results show that the emotional impression of a campaign title, visual information, message quality, and message contents are significantly related to the extent of crowdfunding success. This study provides recommendations for nonprofit social welfare organizations to improve the way in which they operate crowdfunding campaigns and communicate with potential funders.